APPLICATION OF INQUIRY TRAINING LEARNING MODELS WITH MULTIREPRESENTATION OF LEARNING OUTCOMES AND STUDENT PROBLEM SOLVING ABILITIES ON SENIOR HIGH SCHOOL 17 MEDAN - Rina Gunawan Tarigan; Nurliana Marpaung (ISER (Indonesian Science Education Research), 2020)
This study aims to determine the application of the inquiry training learning model with multiple representations of student learning outcomes and problem solving abilities in the subject of Elasticity and Hooke's Law. This study used a quasi experimental method with a two group pretest – posttest research design. The study population was all students of class XI which consisted of 5 classes. The sample was determined by cluster random sampling. Class XI MIA 1 as the experimental class and XI MIA 5 as the control class, each of which consists of 30 students. The instrument used consisted of 10 multiple choice questions for learning outcomes and 5 essay questions for problem solving abilities and had been validated by the validator. The research data shows that the pretest mean value of learning outcomes in the experimental class is 33.00 and the control class was 30.00. Data from the mean pretest of problem-solving ability of the experimental class was 26.22 and the control class was 25.26. The normality and homogeneity tests on the pretest data for the experimental and control classes showed that the data were normally distributed and homogeneous. The t test results showed that the two classes had the same initial ability significantly. After the treatment was carried out in each class, the post-test mean score of learning outcomes in the experimental class was 69.67 and the control class was 58.33. The post-test mean value of problem-solving abilities in the experimental class was 74.52 and the control class was 65.48. The results of hypothesis testing using the t test on student learning outcomes and problem solving abilities showed that learning outcomes and problem-solving abilities were significantly higher in the experimental class than in the control class. The results of data analysis showed that the inquiry training learning model with multiple representations contributed to the scores obtained by students in the experimental class. It can be stated that the inquiry training learning model with multiple representations has an effect on student learning outcomes and problem solving abilities.